A novel method for estimating an individual's deviation from their habitual motion path when running. (2nd September 2019) - Trudeau, Matthieu B.; Willwacher, Steffen; Weir, Gillian; Rohr, Eric; Ertel, Christopher; Bruggemann, Gert-Peter; Hamill, Joseph
Abstract : The current literature on footwear cushioning and pronation has suggested that there may not be a relationship between chronic injury risk and these parameters based on mixed findings and lack of evidence of an association with prospective injury rates. Since footwear has been designed and developed based on cushioning and pronation, we suggest that we have possibly been on a misguided path in footwear design for the last few decades. Current thought thus implies that a new method of footwear prescription is necessary if we are to guide runners toward appropriate footwear that accommodates their individual biomechanical patterns during running. Based on a series of studies investigating the response of the leg to movement and loading patterns, we developed a novel paradigm based on Nigg's 'preferred movement path'. The assumptions of the 'preferred motion path' were modified in the new method and refined as the 'habitual motion path'. We focused on knee motion in addition to foot and ankle motion since the greatest number of injuries to runners is at the knee. We utilized a kinematic method for developing a calculation to determine the deviation of a runner's joint motion path during running from their habitual motion path. We used this deviation as an index for the individual prescription of an appropriate running shoe. While this new method matches a runner based only on their biomechanics, there are other factors that need to be considered. For example, in footwear selection, the individual's training and injury history in addition to the experience that the runner is seeking from their run must also be considered.